Analysis of Wound Healing from Andaliman Fruit Essential Oil Ointment (Zanthoxylum Canthopodium Dc.) on Wistar Rats (Rattus Norvegicus) - Xu Xuliang; Florenly; Johannes Bastira Ginting; Fioni (Britain International for Academic Research (BIAR) Publisher, 2022)
Injuries are cases of injury that are often experienced by every human being. A wound is the loss or damage of some body tissue. Many andaliman fruits contain many phytochemicals such as phenols, saponins, flavonoids, triterpioids, and alkaloids. Its terpenoid content has antioxidant and antimicrobial activity repellents. Iris / incision wounds, which are wounds caused by sharp object slices such as knives, cause damage to vessels that are large enough if the slice is deep enough. This study aims to find out the effect of Andaliman Fruit Essential Oil Saleb (Zanthoxylum acanthopodium DC.) on wound healing in white rats. This experimental study with the approach of Pre-test and Post-test group only control design was conducted January to February 2021, at the Herbarium Medanese FMIPA USU, the Pharmacognosive Laboratory of the Faculty of Pharmacy USU, and the Laboratory of Pharmaceutical Pharmacology USU. The samples were Andaliman Fruit (Zanthoxylum acanthopodium DC.), and male white rats. The number of samples using frederer formula, so determined the number of as many as 25 rats selected randomly divided into 5 groups. Data analysis uses the normality test statistical data test, and the ANOVA test. The results of the study that andaliman fruit extract has several bioactive compounds such as alkaloids, flavonoids, saponins, and tannins that play a role in wound healing. The optimum concentration of Saleb Andaliman fruit essential oil that can heal wounds in white rats is 5%. The highest percentage of cures on the 14th day was in positive control (Bioplacenton®) which was 95% and followed by an extract of 5% v/v with a cure percentage of 90%. Essential oil of andaliman fruit extract has the ability to approach Bioplacenton® in healing wounds in mice.